2021
DOI: 10.1101/2021.03.22.436375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An mRNA vaccine against SARS-CoV-2: Lyophilized, liposome-based vaccine candidate EG-COVID induces high levels of virus neutralizing antibodies

Abstract: In addition to the traditional method of vaccine development, the mRNA coronavirus vaccine, which is attractive as a challenging vaccination, recently opened a new era in vaccinology. Here we describe the EG-COVID which is a novel liposome-based mRNA candidate vaccine that encodes the spike (S) protein of SARS-CoV-2 with 2P-3Q substitution in European variant. We developed the mRNA vaccine platform that can be lyophilized using liposome-based technology. Intramuscular injection of the EG-COVID elicited robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Degradation of mRNA is higher in the presence of water, which makes liposomes less likely to be stable than LNP [14]. Notably, a stable mRNA vaccine was developed with liposomes [42], but it is not known whether the shelf life of liposomal vaccines will be longer than LNP vaccines.…”
Section: Viral and Non-viral Vectorsmentioning
confidence: 99%
“…Degradation of mRNA is higher in the presence of water, which makes liposomes less likely to be stable than LNP [14]. Notably, a stable mRNA vaccine was developed with liposomes [42], but it is not known whether the shelf life of liposomal vaccines will be longer than LNP vaccines.…”
Section: Viral and Non-viral Vectorsmentioning
confidence: 99%
“…Recent studies have shown that LNPs containing small interfering (si) RNA or mRNA can be successfully lyophilized. [8][9][10] Tekmira Pharmaceuticals developed an LNP for treatment of Zaire Ebola virus (ZE-BOV) infection containing siRNA targeting VP24, VP35, and L polymerase proteins. 11,12 After demonstrating complete protection of non-human primates (NHPs) in an otherwise lethal model of ZE-BOV, a reformulated, lyophilized version (TKM-100802) was assessed in a phase 1 clinical trial in 2014 (NCT02041715).…”
Section: Introductionmentioning
confidence: 99%
“…8 Two recent studies demonstrated that the mRNA-LNP platform can also be lyophilized. 9,10 Zhao et al generated lyophilized firefly luciferase-encoding mRNA-LNPs and demonstrated that the reconstituted material maintains the mRNA expression efficiency in mice as observed with in vivo bioluminescence imaging studies. 9 Hong et al developed a lyophilized severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA-LNP vaccine formulation and showed that the reconstituted vaccine can induce strong immune responses in mice.…”
Section: Introductionmentioning
confidence: 99%
“…The study is currently in phase 2/3 clinical trials (ClinicalTrials.gov identifiers NCT04652102 and NCT04674189). A similar vaccine was made by Hong et al using full-length SARS-CoV-2 S-encoding mRNA of the more infectious and fatal variant D614G ( 146 ). The uniqueness of this vaccine is that it can be lyophilized without loss of immunogenicity and is, therefore, highly advantageous for storage and distribution ( 146 ).…”
Section: Bioengineering Strategies Used In Developing Vaccines Against Influenza and Coronavirusesmentioning
confidence: 99%